Productivity of MSME Human Resources during the Covid-19 Pandemic - Don Gusti Rao; Niken Anggun (Budapest International Research and Critics University, 2022)
The Covid-19 pandemic has had an impact on Micro, Small and Medium Enterprises (MSMEs) in Indonesia, one of which is the difficulty in distributing and running their production. This also has an impact on MSMEs implementing work from home (Work from Home) for some employees, especially in the production department, so that an increase in employee productivity is needed. This study aims to find out how strategies and factors influence efforts to increase productivity in MSMEs during the Covid-19 pandemic. Using qualitative methods with interactive data analysis, data collection techniques were carried out by moderate participatory observation and interviews. The data is processed in the form of words or descriptive. The results of the study confirm that in increasing employee productivity, MSME X makes efforts, namely: optimizing the work from home system, training employees, evaluating employee performance directly, and meeting employee needs. In implementing the productivity improvement strategy, there are several obstacles or factors that hinder these efforts, namely: education, employee skills, the environmental situation around employees, and work discipline. Employee productivity during the covid-19 pandemic tends to be stable compared to the beginning of its emergence, namely in March, so it is concluded that the productivity improvement strategy has a positive impact.